The effectiveness of a proposed program for school readiness in developing multiple intelligences for second-grade students in the city of Al-Ahsa? - Mohammed, Aida Theeb; AlZmammi, Reem Merdas; Alsulaiman, Maram Sulaiman (CENTRAL ASIA AND THE CAUCASUS, 2022)
The study aimed to identify the effectiveness of a proposed school readiness program in developing the multiple intelligences of second-grade students in primary school in the city of Al-Ahsa. The researchers used the experimental method, and the study sample consisted of (61) male and female students who were divided into two samples, one experimental and the other a control group. The program consisted of(32) diverse activities. The results of the study showed that there were statistically significant differences between the arithmetic averages of the students’ estimates of the second grade of primary school due to the effectiveness of the proposed program on the pre and post applications in favor of the post application on all intelligences and on the total degree and the absence of statistically significant differences at the level of significance (0.05) between the average ranks of the students for the degree of The possession of second-grade male and female students of behaviors indicative of the types of multiple intelligences , After applying the training program and on the total degree according to the gender variable, except for natural intelligence and personal intelligence and for the benefit of females, the study recommended the importance of paying attention to school readiness programs for their importance and effectiveness in achieving learning goals.